Inquilinus Species Infections in Humans—A Narrative Review - Anastasia Vasilopoulou; Takis Panayiotou; Stella Baliou; Andreas G. Tsantes; Petros Ioannou (Microorganisms)
Background: Inquilinus species are Gram-negative, non-sporulating, non-pigmented rods that are catalase-positive, indole-negative, and able to grow at various temperatures and in 1% NaCl. Infections due to Inquilinus spp. are increasingly identified, especially in patients with cystic fibrosis. Objective: This review aims to present all reported cases of Inquilinus spp. infections in humans, with an emphasis on data regarding epidemiology, antimicrobial resistance, antimicrobial treatment, and mortality. Methods: A narrative review based on a literature search of the PubMed/MedLine and Scopus databases was performed. Results: In total, 13 articles providing data on 25 patients with Inquilinus infections were included in the analysis. The median age was 19 years, while 60% were male. Cystic fibrosis was the predominant risk factor (92%). Respiratory tract infection was the most common type of infection (96%). Inquilinus limosus was the most commonly identified species. Polymicrobial infection was very common (77.3%). Microbial identification required the use of advanced molecular techniques, such as 16s rRNA sequencing. The pathogen exhibited resistance to beta-lactams, with the exception of carbapenems. The most commonly used antimicrobials included carbapenems (68.4%), followed by quinolones (57.9%) and aminoglycosides (52.6%). Mortality was low (4%). Conclusions: Due to the potential of Inquilinus spp. to cause infection in patients with cystic fibrosis, and given the difficulties in microbial identification, clinicians and laboratory professionals should consider it in the differential diagnosis of patients with cystic fibrosis and respiratory tract infection not responding to beta-lactam treatment or with polymicrobial infections, especially when traditional techniques are used for microbial identification.